2022
DOI: 10.1002/aqc.3771
|View full text |Cite
|
Sign up to set email alerts
|

Southern right whale (Eubalaena australis) population demographics at major calving ground Head of Bight, South Australia, 1991–2016

Abstract: 1. Demographic parameters were estimated for southern right whales (SRWs), Eubalaena australis, using photo-identification (photo-ID) and count data collected during annual cliff-based surveys at the Head of the Great Australian Bight (HoB), South Australia between 1991 and 2016. Photo-ID and count data were contributed from the annual aerial surveys of the south-western population in Australia (1993Australia ( -2016. 2. The HoB photo-ID database included 1,186 non-calf individuals, with 459 reproductive femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In South Africa, a suspected climate-driven shift from high-latitude to mid-latitude foraging grounds ( 17 ) coincided with a decline in body condition ( 69 ) and calving rates ( 70 ). SRWs wintering in SW Australia have also experienced a decline in reproductive output coincident with latitudinal shifts in foraging grounds ( 71 ). In contrast, a large proportion of SRWs wintering in the Auckland Islands consistently forages in mid-latitudes near the subtropical front ( 24 ) and has the best body condition score of any right whale population ( 72 ) in addition to having a high population growth rate ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, a suspected climate-driven shift from high-latitude to mid-latitude foraging grounds ( 17 ) coincided with a decline in body condition ( 69 ) and calving rates ( 70 ). SRWs wintering in SW Australia have also experienced a decline in reproductive output coincident with latitudinal shifts in foraging grounds ( 71 ). In contrast, a large proportion of SRWs wintering in the Auckland Islands consistently forages in mid-latitudes near the subtropical front ( 24 ) and has the best body condition score of any right whale population ( 72 ) in addition to having a high population growth rate ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although these long‐term SRW photo‐identification data sets have been revealing the steady recovery of the species since whaling ended, the last decade has seen some unprecedented changes. Most interestingly, coastal prevalence has started to fluctuate enormously, and calving intervals have increased in the populations calving off Argentina, South Africa, and Australia (Charlton, 2017; Marón et al, 2015; Vermeulen et al, 2019, 2020). Furthermore, additional research revealed that in the South African SRW population, maternal body condition decreased by around 23% over the past two decades (Vermeulen et al, 2023) concurrent with a shift in foraging behavior (van den Berg et al, 2021).…”
Section: Whale Id Deployment Date Last Position Date Duration (Days) ...mentioning
confidence: 99%
“…The research was undertaken to address several priority research questions identified in the Australian Conservation Management Plan for SRWs, specifically to better understand offshore distribution and migration pathways (DSEWPaC 2012, Mackay et al 2020). The population demographics of the south-western population are well understood, and long-term monitoring has been undertaken through aerial and cliff-based research since the early nineties (Charlton et al 2022, Smith et al 2022. The south-western Australian population has an estimated abundance of 2549 individuals (Smith et al 2022), and the observed mean calving interval is 3.9 yr (95% CI: 3.8, 4.1) (Charlton et al 2021).…”
Section: Introductionmentioning
confidence: 99%